2022
DOI: 10.1200/jco.21.02543
|View full text |Cite
|
Sign up to set email alerts
|

Joint Final Report of EORTC 26951 and RTOG 9402: Phase III Trials With Procarbazine, Lomustine, and Vincristine Chemotherapy for Anaplastic Oligodendroglial Tumors

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the basis of the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. Anaplastic oligodendroglial tumors (AOTs) are chemotherapy-sensitive brain tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 28 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…87 A watch and wait approach with regular MRI surveillance may be appropriate for younger patients with a WHO grade 2 IDH-mutant glioma, minimal residual disease, and no neurologic symptoms related to the tumor, with the goal to delay treatment-associated adverse effects (eg, fatigue, short-term memory loss). Post hoc analysis of the cooperative group NRG Oncology/Radiation Therapy Oncology Group (RTOG) 9802 67 showed that patients with high-risk IDH-mutant WHO grade 2 glioma (ie, patients aged 40 years and older or with subtotal resections) benefited from the addition of procarbazine, lomustine, and vincristine to radiotherapy (IDH-mutant 1p/19q codel [37 patients]; overall survival, 13.9 years [radiotherapy] vs not 68 Both EORTC 26951 and RTOG 9402 studies demonstrated a progressionfree survival of more than 30% at 20 years in patients with 1p/19q codeletion, indicating that durable disease control was feasible with this regimen. Procarbazine, lomustine, and vincristine also improved overall survival for patients with IDH-mutant tumors without 1p/19q codel, 68 consistent with the results from RTOG 9802.…”
Section: Treatment Of Idh-mutant Astrocytoma and Oligodendrogliomamentioning
confidence: 99%
See 2 more Smart Citations
“…87 A watch and wait approach with regular MRI surveillance may be appropriate for younger patients with a WHO grade 2 IDH-mutant glioma, minimal residual disease, and no neurologic symptoms related to the tumor, with the goal to delay treatment-associated adverse effects (eg, fatigue, short-term memory loss). Post hoc analysis of the cooperative group NRG Oncology/Radiation Therapy Oncology Group (RTOG) 9802 67 showed that patients with high-risk IDH-mutant WHO grade 2 glioma (ie, patients aged 40 years and older or with subtotal resections) benefited from the addition of procarbazine, lomustine, and vincristine to radiotherapy (IDH-mutant 1p/19q codel [37 patients]; overall survival, 13.9 years [radiotherapy] vs not 68 Both EORTC 26951 and RTOG 9402 studies demonstrated a progressionfree survival of more than 30% at 20 years in patients with 1p/19q codeletion, indicating that durable disease control was feasible with this regimen. Procarbazine, lomustine, and vincristine also improved overall survival for patients with IDH-mutant tumors without 1p/19q codel, 68 consistent with the results from RTOG 9802.…”
Section: Treatment Of Idh-mutant Astrocytoma and Oligodendrogliomamentioning
confidence: 99%
“…Post hoc analysis of the cooperative group NRG Oncology/Radiation Therapy Oncology Group (RTOG) 9802 67 showed that patients with high-risk IDH-mutant WHO grade 2 glioma (ie, patients aged 40 years and older or with subtotal resections) benefited from the addition of procarbazine, lomustine, and vincristine to radiotherapy (IDH-mutant 1p/19q codel [37 patients]; overall survival, 13.9 years [radiotherapy] vs not 68 Both EORTC 26951 and RTOG 9402 studies demonstrated a progressionfree survival of more than 30% at 20 years in patients with 1p/19q codeletion, indicating that durable disease control was feasible with this regimen. Procarbazine, lomustine, and vincristine also improved overall survival for patients with IDH-mutant tumors without 1p/19q codel, 68 consistent with the results from RTOG 9802. Temozolomide is an acceptable alternative to procarbazine, lomustine, and vincristine.…”
Section: Treatment Of Idh-mutant Astrocytoma and Oligodendrogliomamentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of median 18-19 years of follow-up duration, the authors exhibited that progression-free survival of oligodendroglioma could be significantly improved by PCV plus RT. 1 Briefly, the study provides impressive results of two important and large-scale analyses were performed in random-effects models with Stata software (version 12.0 7 ). Heterogeneity across meta-analyses was calculated via Cochran Q chi-square test, a derived I 2 statistic .…”
mentioning
confidence: 99%
“…6 Then, we noticed some important but unstable results because the 95% CI was quite close to 1, such as overall survival (OS) on oligodendroglioma in EORTC 26951 (hazard ratio, 0.60; 95% CI, 0.35 to 1.03) and OS on isocitrate dehydrogenase-mutant astrocytoma in RTOG 9402 (hazard ratio, 0.60; 95% CI, 0.34 to 1.03). 1 Given the vulnerability of the results provided, we performed a mini meta-analysis of the two trials by using a randomeffects model 1 and revealed that PCV plus RT could significantly improve both OS and progression-free survival in all patients with grade 3 oligodendroglioma and isocitrate dehydrogenase-mutant astrocytoma (all P , .05; Fig 1). Through mini meta-analysis, we further confirmed the results of the current study in a more robust and reliable manner.…”
mentioning
confidence: 99%